Pedestrian Space Characteristics Analysis on Kyai Tapa-KH. Hasyim Ashari Street Corridor, West Jakarta - Quintarina Uniaty (Graduate Program of Syiah Kuala University, 2017)
The city of Jakarta shows special characteristics in social, economic and cultural structures, a characteristic of urban life that gives much influence to its physical form. Development of the city is faced with problem of environmental degradation caused by unbalanced provision of urban infrastructure and facilities against the heterogeneity of urban needs and activities. The services provided by municipal government are more often unable to keep up with increasing demands of society's needs. Urban spatial and specific facilities built to expect community activities in accordance with the facilities built.This paper aims to put forward the results of studies that have been done about public perception use of pedestrian and public space area at object study, the characteristics of user's activities area region object of research and empirical data about the problem of pedestrian path as part of a public space that is related to behavior of community activity. The research method is Descriptive Analysis as a research that suggests the phenomenon that occurs and see and seek interrelations. It is a combination of descriptive survey method with analytical survey method of a phenomenon. Case studies presented as an object of analysis at a later stage, to be able to better explain the facts found and influence between variables. Built environment as product and work in form of space, volume, structure, ornament; needed as a message representing the norms and values of society, perceptions and aspirations, including developing their motivations and expectations explicitly or implicitly. City life activities require pedestrian space adapted to the aspirations of its people, as an effort to humanize pedestrians into the pedestrian area planning as a spatial dimension in urban area physical development.